Publicité télévisée sur les aliments visant les enfants québécois - Estelle Lebel; Anne-Marie Hamelin; Marguerite Lavallée; Annie Bédard; Amélie Dubé (Communication)
The importance of the content of advertising in television programming aimed at children has long been an object of social preoccupation. In the study presented here, the content of food advertising to which Québécois children are exposed daily is analyzed from the dual points of view of nutrition and communication. The analysis of these contents allows us to identify the types of products advertised, the frequency and timing of their diffusion, the nutritional composition of the food advertised, and the socio-cultural values, which are associated with them.